Między oddaniem a ślepym posłuszeństwem. Literacka kreacja psa w wybranych utworach niemieckojęzycznych - Głuszko-Boczoń, Estera (Zoophilologica. Polish Journal of Animal Studies, 2016)
The aim of this paper is to examine the multidimensional way of presenting dogs in selected German works. Dogs trigger a whole range of emotions in man, such as attachment and protectiveness, but also the dangerous instinct associated with the desire for power and domination. Dogs can be both devoted companions and friends to man but also objects of ruthless training. Therefore, Theodor Fontane’s and Thomas Mann’s works, which present the function of animals in a surprising light, may be an excellent point of reference.